Avaliação socioeconômica do Projeto Agente Rural no Contexto do Fundo Estadual de Combate a Pobreza do Ceará, Município de Granja, 2004/2008 - Santos, Wilmar Bezerra dos (2010)
This thesis consists of an evaluation of the Rural Agent Project, financed with funds from a Public Policy to combat the developing poverty in the state of Ceará since 2003 with the creation of the State Fund to Combat Poverty (Fundo Estadual de Combate à Pobreza) – FECOP . Its action focus is "to fight poverty, to reduce income inequality and to promote growth with social inclusion" and its target group are the families who are below the poverty line, living in areas characterized by serious social indicators. In a correlation between the focus established by the referred public policy and the purpose of the Agent Rural Project, which is: “To ensure social inclusion of rural families in the state of Ceará by transforming agriculture, with the increase of production and income, by increasing productivity, through the contribution, ownership and development of technical and managerial knowledge, through the organization of farmers into associations and the leverage of the small and micro rural enterprises”, it was possible to verify the changes and their reflections on the life of family-based farmers in the town of Granja-CE., period 2004/2008.Still, we defined a second line of studies about the achievements of the Evaluation of Public Policies. In this approach, we combine studies in order to build the theoretical bases that promote the construction of an object of study, based on the discussion of possibilities of restoring the citizenship with the reduction of poverty and social inequality through public policies of sustainable development, taking as investigation reference the FECOP / Agent Rural Project executed by the State of Ceará since 2003. For the analysis of this object, it was developed an evaluative study of quantitative and qualitative nature, working on secondary data from the survey of the FECOP, IBGE, IPECE publications, UFC, SDA and extensive bibliography on the subject, complemented by primary data collected through questionnaires and semi-structured interviews. The evaluative study of FECOP / Agent Rural Project presented in this thesis showed its importance while involving all those partners responsible for the implementation of the proposal, such as technicians, beneficiaries, society, trade unions (STTR) and the municipal and state governments (managers).When we asked about the importance and maintenance of this policy, we obtained almost 100% "yes" responses. However, the study also revealed limitations in the scope of the project, given the insufficient number of technicians to meet the needs and the fluctuating hiring, causing insecurity for the professional. Another limiting factor was the lack of integration with other public policies, especially in the area of qualification and programs that provide Technical Assistance. As to the results of the study, there are suggestions regarding the design of policy in order to reconsider the way technicians for temporary jobs are hired; thus, reducing the vulnerability of the worker, as well increasing the number of Rural Agents, promotion of technical / producer training in the area of organization and that state / province comply with their responsibilities with regard to parity of the recruitment of Rural agents.